Socialist Realism Sculptures : Reflecting Society And Culture In The Socialist Republic Of Vietnam (Journal of Namibian Studies : History Politics Culture, 2023)
This study sought to investigate social and cultural reflections presented in socialist realism sculptures in the Socialist Republic of Vietnam. The sample of the study was selected by means of purposive sampling and the data was analyzed through structural functionalism, historicism, aesthetics, mythologies, and the reflection theory. The results showed that the sculptures portrayed five aspects of social reflections, including politics and governance, economy, family and lifestyles, education, and history, as well as four aspects of cultural reflections, such as clothing, tools, games and music, and values. Additionally, social reflections were more prevalent than cultural ones due to the inspiration for the sculptures being derived from stories of social and historical events, revolution and war, and Vietnamese lifestyles. The creation of the sculptures was also influenced by the communist party’s policies, so the presented contents must be in line with its operation to ensure the same direction towards success.